2013
DOI: 10.1111/irv.12182
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis of pandemic A(H1N1) 2009 influenza in children with negative rapid influenza diagnostic test by lymphopenia and lower C‐reactive protein levels

Abstract: BackgroundThe sensitivity of rapid influenza diagnostic test (RIDT) of children with influenza-like illness (ILI) remains low.ObjectiveWe compare the parameters between pandemic A(H1N1) 2009 influenza with negative RIDT and ILI not H1N1 for improving the low sensitivity of RIDT for children with ILI.MethodsIn a cohort of consecutive laboratory-confirmed H1N1 influenza, we identified 150 H1N1 children with positive RIDT, 152 H1N1 children with negative RIDT, and 75 children with ILI not H1N1. Viral load in thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
0
14
1
1
Order By: Relevance
“…Although immunoglobulins may play an important role in the innate immune response during ARDS, nonspecific immunoglobulins may not be as effective in a lymphopenia environment. Lymphopenia has been described in ARDS patients and in animal models after viral infection or mycoplasma infection and affects all lymphoid tissue [26][27][28]. However, in our small group of non-survivors, the percentage of lymphocytes rather than impaired kinetics over time was impressive.…”
Section: Discussionmentioning
confidence: 59%
“…Although immunoglobulins may play an important role in the innate immune response during ARDS, nonspecific immunoglobulins may not be as effective in a lymphopenia environment. Lymphopenia has been described in ARDS patients and in animal models after viral infection or mycoplasma infection and affects all lymphoid tissue [26][27][28]. However, in our small group of non-survivors, the percentage of lymphocytes rather than impaired kinetics over time was impressive.…”
Section: Discussionmentioning
confidence: 59%
“…The present ndings showed that CRP greater more than 100 mg/L was signi cantly associated with case fatality. A signi cant increase in CRP levels, as documented for bacterial infections, can also occur with viral infections [15]. It is well known that CRP is a classic acute phase protein.…”
Section: Discussionmentioning
confidence: 94%
“…Lymphocytopenia is more closely associated with viral infections. 28 The presence of increased leukocytes and neutrophils may be associated with the heterogeneous inflammatory response, possibly attributable to preexisting inflammation due to asthma that might be worsened by exposure to the virus. Production of chemokines by bronchial epithelium in response to a viral infection leads to the entry of neutrophils to the respiratory airways, as confirmed on experimental and naturally induced common cold among asthmatic patients.…”
Section: Discussionmentioning
confidence: 99%